Salmonella Hepatitis - A Case Report (Global Journal of Medical Research, 2020)
Salmonella hepatitis is a rare complication of Typhoid fever in tropics. Typhoid fever is an infectious disease associated with high morbidity and mortality. The classical pattern of presentation is continuous fever with a "step ladder" rise, headache, abdominal pain, diarrhea, constipation, and relative bradycardia. In a rare instance, Typhoid fever presented with the feature of acute hepatitis like hepatomegaly and deranged liver functions with hepatic encephalopathy. After taking proper informed consent, we have reported a young patient who presented with low-grade fever, diarrhea, and jaundice. Subsequently he was found to have acute salmonella hepatitis secondary to typhoid fever. Recognition of Salmonella hepatitis is of clinical importance as it can mimic acute viral hepatitis. Early institution of specific therapeutic intervention and supportive care improve the prognosis in these patients.
Keywords: typhoid fever; salmonella hepatitis; typhoid hepatitis